2012
DOI: 10.4236/fns.2012.38146
|View full text |Cite
|
Sign up to set email alerts
|

Jamun (<i>Syzygium cumini </i>(L.)): A Review of Its Food and Medicinal Uses

Abstract: Eugenia jambolana Lam., commonly known as black plum or "jamun" is an important medicinal plant in various traditional systems of medicine. It is effective in the treatment of diabetes mellitus, inflammation, ulcers and diarrhea and preclinical studies have also shown it to possess chemopreventive, radioprotective and antineoplastic properties. The plant is rich in compounds containing anthocyanins, glucoside, ellagic acid, isoquercetin, kaemferol and myrecetin. The seeds are claimed to contain alkaloid, jambo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
55
0
6

Year Published

2016
2016
2023
2023

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 85 publications
(62 citation statements)
references
References 112 publications
(75 reference statements)
1
55
0
6
Order By: Relevance
“…The presence of quercetin in Java plum seed was confirmation of previous researches (Baliga et al, 2011;Swami et al, 2012). Flavonoid tends to dissolve in water and other polar solvents such as methanol, ethanol, ethyl acetate and their mixture, which classified them as a suitable solvent to extract plant flavonoid (Heim et al 2002;Harborne, 2006;Durackova, 2008).…”
Section: Identification Of Phenolic Compounds Using Hplc-dadsupporting
confidence: 50%
See 2 more Smart Citations
“…The presence of quercetin in Java plum seed was confirmation of previous researches (Baliga et al, 2011;Swami et al, 2012). Flavonoid tends to dissolve in water and other polar solvents such as methanol, ethanol, ethyl acetate and their mixture, which classified them as a suitable solvent to extract plant flavonoid (Heim et al 2002;Harborne, 2006;Durackova, 2008).…”
Section: Identification Of Phenolic Compounds Using Hplc-dadsupporting
confidence: 50%
“…Previous researches showed that the seed contains glycoside, hoursbolin (antimellin), ellagic acid, alkaloid (Quisumbing, 1951;Parmar et al, 2010), gallic acid, galloylglucose, 3-galloylglucose, 3,6-hexahydroxy diphenoylglucose, 4,6 hexahydroxydiphenoylglucose and β-sitosterol (Helmstadter, 2008;Swami et al, 2012;Rydlewsky et al, 2013). A research reported kaempferol and epicatechin claimed as first publication reported epicatechin content of Java plum seed (Rydlewsky et al, 2013).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Delphinidin inhibited the phosphorylation of protein kinases in ERK/JNK signaling pathways leading to suppression of AP-1 transactivation. In case of UV-irradiated cancer, cyclooxygenase-2 expression was suppressed through inhibition of MAPKK4 and PI-3 kinase (Swami et al, 2012). The extract could effectively act against early stage HCT-116 human colon cancer cells and also triggered apoptosis and prevented self-renewal of colon cancer stem cells.…”
Section: Indian Blackberrymentioning
confidence: 95%
“…Development of skin carcinogenesis induced by chemicals and UV-rays could be remarkably suppressed. It also exhibits radioprotective effect (Swami et al, 2012;Muniappan and Panduragan, 2012;Ayyanar and Subhas babu, 2012).…”
Section: Description Of Fruits and Spectrum Of Pharmacological Activimentioning
confidence: 99%